PENGUNGKAPAN BIAYA SOSIAL SEBAGAI BENTUK PERTANGGUNGJAWABAN SOSIAL PERUSAHAAN TERHADAP LINGKUNGAN SEKITAR - Rahayu, Aminarti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
In conducting the companyâs operating activities, a company not only to find a profit but must be contributed tothe public or environment by improving the quality of life of the community and the environment. The purposeof this study is to investigate the implementation of CSR programs in East Java PT Graha Utama, to know whatare the social costs incurred by PT Graha Java Home as a form of social responsibility, and to know the socialresponsibility accounting reports that are useful to assess the performance of the companys social activities. PTJatim Grha Utama has not made social activities report, so that in order to find out the social costs which hasbeen issued by the company may pay attention to the income and loss report company. From the social activityreport can be measured the performance of companyâs social activities to the environment. The result of thisresearch shows that the PT Jatim Grha Utama already implements the CSR program even though in itsimplementation has not made the formation of the program itself, especially The Partnership and CommunityDevelopment Program. The form of the social activity that has been performed by PT Jatim Grha Utama dividedinto three which are public contribution, the human resource department contribution, and the enviromentcontribution. The proportion of the social costs to the fixed profit in the year of 2010 as much as 2.16% and inthe year of 2011 as much as 2,51%.Keywords: Social Costs, Corporate Social Responsibility, Social Activity, and Social Contribution